How can early life adversity still exert an effect decades later? A question of timing, tissues and mechanisms - Mposhi, Archibold; Turner, Jonathan D. (Frontiers in Immunology, 2023)
Exposure to any number of stressors during the first 1000 days from conception to age 2 years is important in shaping an individual’s life trajectory of health and disease. Despite the expanding range of stressors as well as later-life phenotypes and outcomes, the underlying molecular mechanisms remain unclear. Our previous data strongly suggests that early-life exposure to a stressor reduces the capacity of the immune system to generate subsequent generations of naïve cells, while others have shown that, early life stress impairs the capacity of neuronal stem cells to proliferate as they age. This leads us to the “stem cell hypothesis” whereby exposure to adversity during a sensitive period acts through a common mechanism in all the cell types by programming the tissue resident progenitor cells. Furthermore, we review the mechanistic differences observed in fully differentiated cells and suggest that early life adversity (ELA) may alter mitochondria in stem cells. This may consequently alter the destiny of these cells, producing the lifelong “supply” of functionally altered fully differentiated cells.